Functional Genomics Uncovers Pleiotropic Role of Rhomboids in Corynebacterium glutamicum - Luenenschloss, Andrea; ter Veld, Frank; Albaum, Stefan P.; Neddermann, Tobias M.; Wendisch, Volker F.; Poetsch, Ansgar (Frontiers in Microbiology, 2022)
The physiological role of ubiquitous rhomboid proteases, membrane-integral proteins that cleave their substrates inside the lipid bilayer, is still ill-defined in many prokaryotes. The two rhomboid genes cg0049 and cg2767 of Corynebacterium glutamicum were deleted and it was the aim of this study to investigate consequences in respect to growth phenotype, stress resistance, transcriptome, proteome, and lipidome composition. Albeit increased amount of Cg2767 upon heat stress, its absence did not change the growth behaviour of C. glutamicum during exponential and stationary phase. Shotgun mass spectrometry permitted the quantification of on average 850 proteins in the cytoplasmic and membrane fraction, respectively. Cluster analyses of protein abundances revealed that rhomboids shape the proteome in a broad range of cellular functions, and affect protein abundances more in the stationary than exponential growth phase. An observation common to both growth phases was a decrease in ribosomal subunits and RNA polymerase, differences in iron uptake proteins, and abundance changes in lipid and mycolic acid biosynthesis enzymes that suggested a functional link of rhomboids to cell envelope lipid biosynthesis. The latter was substantiated by shotgun lipidomics in the stationary growth phase, where in a strain-dependent manner phosphatidylglycerol, phosphatidic acid, diacylglycerol and phosphatidylinositol increased irrespective of cultivation temperature.